Proceedings 2018 Network and Distributed System Security Symposium 2018
DOI: 10.14722/ndss.2018.23165
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cooling Redundancy: A New Security Vulnerability in a Hot Data Center

Abstract: Abstract-Data centers have been growing rapidly in recent years to meet the surging demand of cloud services. However, the expanding scale and powerful servers generate a great amount of heat, resulting in significant cooling costs. A trend in modern data centers is to raise the temperature and maintain all servers in a relatively hot environment. While this can save on cooling costs given benign workloads running in servers, the hot environment increases the risk of cooling failure. In this paper, we unveil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Finally, thermal information can also be used as a proxy estimate for power consumption in data centers. This information can alert potential adversaries to opportune moments to attack the availability of servers, either by exceeding the power capacity [21], or by more generally degrading performance [7]. Although these attacks require privileged thermal sensors, FPGA ROs could also be used for similar purposes, complementing our work in this paper.…”
Section: B Power and Temperature Covert Channelsmentioning
confidence: 90%
“…Finally, thermal information can also be used as a proxy estimate for power consumption in data centers. This information can alert potential adversaries to opportune moments to attack the availability of servers, either by exceeding the power capacity [21], or by more generally degrading performance [7]. Although these attacks require privileged thermal sensors, FPGA ROs could also be used for similar purposes, complementing our work in this paper.…”
Section: B Power and Temperature Covert Channelsmentioning
confidence: 90%
“…Cloud security has received much attention from both academia [18] and industry. Co-residence detection in the cloud settings is the most closely related research topic to our work.…”
Section: Cloud Security and Side/covert Channel Attacksmentioning
confidence: 99%
“…Complacency could lead to the belief that the facility has more time than required to get data center running again, but this can be risky. Gao et al [15] unveiled a new vulnerability of existing data centers with aggressive cooling energy saving policies, conducted thermal experiments, and uncovered effective thermal models at the data center, rack, and server levels. The results demonstrated that thermal attacks can largely increase the temperature of victim servers degrading their performance and reliability, negatively impacting on thermal conditions of neighboring servers causing local hotspots, raising the cooling cost, and even leading to cooling failures.…”
Section: Literature Reviewsmentioning
confidence: 99%